2016
DOI: 10.1186/s40413-016-0126-z
|View full text |Cite
|
Sign up to set email alerts
|

Local allergic rhinitis: entopy or spontaneous response?

Abstract: BackgroundThe existence of a local allergic rhintis was proposed on the basis of the detection of nasal IgE in the absence of a systemic sensitization. Nevertheless, the significance of this phenomenon remains still unclear.We assessed the presence of mucosal nasal IgE in patients with ascertained allergic rhinitis, nonallergic rhinitis with inflammation and in healthy controls.MethodsConsecutive patients with a well ascertained diagnosis (clinical history, skin prick test, specific IgE assay, nasal endoscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…[71], yet not all of them have been applied to LAR. Therefore, nasal sIgE should be regarded mostly as a research tool, which cannot be recommended for routine LAR diagnosis [75,76,77].…”
Section: Diagnosismentioning
confidence: 99%
“…[71], yet not all of them have been applied to LAR. Therefore, nasal sIgE should be regarded mostly as a research tool, which cannot be recommended for routine LAR diagnosis [75,76,77].…”
Section: Diagnosismentioning
confidence: 99%
“…It is not certain whether LAR is a separate condition or merely an “introduction” to the development of the classic allergic rhinitis. Research by Gelardi et al suggests that local production of IgE may be a part of a nonspecific immune response to environmental factors, and the researchers recommend that great care should be taken in the diagnosis of LAR [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For now, it is not clear whether nasal allergen specific IgE production in LAR is secondary to local sensitization or a spontaneous immune response. It is shown that nasal allergen specific IgE may be found in about 50% of the healthy control subjects and we believe that our hypothesis may bring a new point of view to the conflicting concept of LAR [ 4 ]. Although our case also states the importance of the objective demonstration of allergen sensitization in different skin areas which will enable anti-IgE treatment opportunity in patients with severe asthma and rhinitis with low levels of specific IgEs and negative SPTs.…”
Section: Discussionmentioning
confidence: 99%